'Ethics Between the Lines' - Nurses' Experiences of Ethical Challenges in Long-Term Care - Hilde Munkeby; Aud Moe; Grete Bratberg; Siri A. Devik (SAGE Publishing, 2021)
In long-term care, ethical challenges are becoming increasingly apparent as the number of older patients with complex care needs increases, in parallel with growing demands for more cost-efficient care. Scarce resources, cross-pressure and value conflicts are associated with missed care, moral stress and nurses wanting to leave the profession. Through five focus group interviews, this study aimed to explore how nurses working in nursing homes and homecare services perceive, experience and manage ethical challenges in everyday work. Content analysis revealed three main themes: striving to do good; failing and being let down and getting rid of frustrations and learning from experiences. The nurses' morality was mainly expressed through emotions that arose in specific situations. Dedicated spaces for ethical reflection and leaders who recognize that organizational conditions affect the individual nurse-patient relationship are required. Facilitating ethical reflection is an important leadership responsibility, which may also require leaders to actually participate.